IMPLEMENTATION OF CONTRACTS IN ONLINE BUYING AND SELLING TRANSACTION ON TIKTOK SHOP FIQH MUAMALAH PERSPECTIVE - Muhammad Basri; Sri Yuniati (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2026)
The development of the digital economy has driven transformation in buying and selling practices, one of which is through the TikTok Shop platform which integrates social media and e-commerce. This study aims to analyze the implementation of contracts in online buying and selling transactions on TikTok Shop and assess its suitability with the principles of fiqh muamalah. This research uses a qualitative approach with the type of library research, with data sources in the form of fiqh muamalah literature, scientific journals, and documents related to digital transaction mechanisms. The data analysis technique is carried out through the content analysis method and the descriptive-analytical approach. The results of the study show that the implementation of the contract in TikTok Shop has basically met the principles and requirements of the contract, even though it has undergone transformation in the form of ijab and qabul which is carried out digitally. However, there are several aspects that still need attention, such as the potential for gharar due to the lack of clarity of product information, affiliate marketing practices that have the potential to contain elements of tadlis, and payment systems that resemble salam contracts but do not fully meet the principle of clarity. In addition, the consumer protection mechanism has reflected the concept of khiyar rights, but its implementation has not been optimal. This study concludes that the practice of buying and selling on TikTok Shop can be categorized as muamalah that is allowed as long as it meets sharia principles, such as honesty, transparency, and fairness. Therefore, it is necessary to increase awareness and responsibility from all parties so that digital transactions can run in accordance with the values of fiqh muamalah. This research is expected to contribute to the development of sharia economic studies, especially in responding to the dynamics of the contemporary digital economy.